2020
DOI: 10.3390/jcm9061873
|View full text |Cite
|
Sign up to set email alerts
|

Course of Adverse Events during Short Treatment Regimen in Patients with Rifampicin-Resistant Tuberculosis in Burundi

Abstract: The introduction of the nine-month short-treatment regimen (STR) has drastically improved outcomes of rifampicin-resistant tuberculosis (RR-TB) treatment. Adverse events (AE) commonly occur, including injectable-induced hearing loss. In Burundi we retrospectively assessed the frequency of adverse events and treatment modifications in all patients who initiated the STR between 2013–2017. Among 225 included patients, 93% were successfully treated without relapse, 5% died, 1% was lost-to-follow-up, 0.4% had treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
3
14
0
1
Order By: Relevance
“…Such a pattern might be explained in that some DAE, such as ototoxicity, commonly are observed in patients receiving large cumulative doses of second-line injectable drug [ 4 ], while sharp decline between month 5 and 6 reflects the phasing out of the intensive phase of treatment. A similar pattern was shown among hospitalized RR-TB patients receiving conventional individualized treatment in Tashkent [ 33 ], but in other STR studies the median time to AE was reported earlier, usually during the first two months of treatment [ 11 , 32 , 34 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Such a pattern might be explained in that some DAE, such as ototoxicity, commonly are observed in patients receiving large cumulative doses of second-line injectable drug [ 4 ], while sharp decline between month 5 and 6 reflects the phasing out of the intensive phase of treatment. A similar pattern was shown among hospitalized RR-TB patients receiving conventional individualized treatment in Tashkent [ 33 ], but in other STR studies the median time to AE was reported earlier, usually during the first two months of treatment [ 11 , 32 , 34 ].…”
Section: Discussionsupporting
confidence: 75%
“…In our study, grade 3 or 4 DAE occurred in 22.1% (95%CI 14.2–31.9%) of participants. This is much higher compared to STR observational studies conducted in nine countries in Africa (10.7%) [ 9 , 11 ], Niger (6.6%) [ 26 ] and Burundi (4%) [ 32 ], but much lower compared to the 48.2% of grade 3–4 AE reported in the STR arm in the STREAM trial [ 25 ]. Our results are consistent with previous publications showing 21.9% grade 3 or 4 AE among RR-TB patients enrolled in STR in Karakalpakstan [ 13 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In Burundi, the Rifampicin resistant tuberculosis (RR-TB) treatment started in 201 3[ 19 ]. Nine month short-treatment regimen improved outcomes of RR-TB treatment with only 8.2% of treatment failure [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Burundi, the Rifampicin resistant tuberculosis (RR-TB) treatment started in 201 3[ 19 ]. Nine month short-treatment regimen improved outcomes of RR-TB treatment with only 8.2% of treatment failure [ 19 ]. Despite evident progress,recent survey have shown that only half of cases are detected, DR-TB form are spreading [ 20 ]…”
Section: Introductionmentioning
confidence: 99%